Pengaruh Pengetahuan, Tingkat Pendapatan, dan Persepsi Terhadap Minat Wanita Usia Subur Untuk Melakukan Screening Kanker Serviks di Puskesmas Wanajaya Bekasi Tahun 2023 - Putri, Priana Dewi (Lembaga Publikasi Ilmiah Nusantara, 2024)
This research aims to determine the relationship between knowledge, income level, and perception towards the interest of women of reproductive age in cervical cancer screening at the Wanajaya Public Health Center in Bekasi. The type of research used is quantitative research with an analytic cross-sectional study approach, and bivariate data analysis will use the Chi-Square test. This research was conducted in December 2022. The data used in this study is primary data with 100 women of reproductive age as respondents. The research results showed that out of 100 women of reproductive age, 81 women (81%) had good knowledge, while 19 women (19%) had insufficient knowledge about cervical cancer screening. As for income levels, 53 women (53%) had a sufficient income level, while 47 women (47%) had a lower income level. Regarding perceptions of cervical cancer screening, 9 women (9%) had good perceptions, 41 women (41%) had moderate perceptions, and 50 women (50%) had poor perceptions. The statistical test results using Chi-Square showed a very significant relationship between income level and interest in cervical cancer screening, with a P-value of 0.000 ≤ 0.05. From the analysis, the relationship between knowledge and interest in cervical cancer screening also showed a very high potential, with an Odds Ratio (OR) = 7.758 (2.092-28.761), meaning that women of reproductive age with good knowledge are 7.758 times more likely to be interested in cervical cancer screening compared to those with insufficient knowledge.